2013
DOI: 10.1097/nur.0b013e3182a872e3
|View full text |Cite
|
Sign up to set email alerts
|

A Sociotechnical Approach to Successful Electronic Health Record Implementation

Abstract: Rising healthcare costs coupled with patient safety considerations and quality of care have become major concerns for healthcare purchasers, providers, and policymakers. Health information technology, particularly the electronic health record (EHR), is posed as a solution to address these concerns by delivering greater efficiencies and improved quality of care. Despite the national movement toward EHR adoption, successful EHR implementation continues to be challenging for many healthcare organizations, both la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…However, EHR implementation is a complex and challenging organizational change which is often resisted with planned or actual boycotts, and workarounds by medical staff to state-ofthe-art systems [3,4].Although failures are not commonly reported in literature [3], it is estimated that 50-75% of implementations of EHRs and other health information technologies fail-i.e. they overrun budgets or implementation time, do not provide end user satisfaction, or are completely abandoned [3][4][5][6][7].Implementation of EHRs is difficult because it is not merely a technological change, but rather a socio-technical change process that affect many aspects of the organization [8][9][10]. It often results into changes or disruptions in clinical workflows, introduction of extra tasks, or shifting of tasks from one cadre to another [3][4][5]11,12] e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, EHR implementation is a complex and challenging organizational change which is often resisted with planned or actual boycotts, and workarounds by medical staff to state-ofthe-art systems [3,4].Although failures are not commonly reported in literature [3], it is estimated that 50-75% of implementations of EHRs and other health information technologies fail-i.e. they overrun budgets or implementation time, do not provide end user satisfaction, or are completely abandoned [3][4][5][6][7].Implementation of EHRs is difficult because it is not merely a technological change, but rather a socio-technical change process that affect many aspects of the organization [8][9][10]. It often results into changes or disruptions in clinical workflows, introduction of extra tasks, or shifting of tasks from one cadre to another [3][4][5]11,12] e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Electronic health record (EHR) systems have increasingly replaced paper-based practices in hospitals, with the expectation of providing many clinical and organizational benefits [1,2]. Implementation of EHRs will inevitably change work practices in health care [3,4] and, if not properly managed, may result in many unexpected and unintended consequences. In addition to the benefits identified (eg, reduction of medication errors), health care professionals have reported disadvantages, such as increased emotional strain and increased errors when trying to learn and adapt to new technologies and managing their workflow disruptions [2,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The study is underpinned by the socio-technical systems theory, which has been suggested as an appropriate framework with which to evaluate Health Information Technology (HIT) such as the EPR [ 33 35 ]. This paradigm states that ‘organisational and human (socio) factors and information technology system factors (technical) are inter-related parts of one system, each shaping the other’ [ 36 ].…”
Section: Methodsmentioning
confidence: 99%